The Politics of International Trade - Wilfred J. Ethier; Arye L. Hillman (Center for Economic Studies and ifo Institute (CESifo), 2017)
Traditional international trade models explain comparative advantage and describe aggregate gains for a country from trade and from terms-of-trade improvement but do not address the politics of international trade policy. A positive or predictive model that studies the politics of trade policy requires two premises, both with public choice origins: (1) that political self-interest underlies policy determination of trade policy rather than social-welfare objectives, and (2) politically assignable rents are preferred to budgetary revenue from trade restrictions and aggregate gains from terms-of-trade improvement. Originating political-economy models of protectionism and reciprocal trade liberalization acknowledge on both premises. Subsequent popular (and popularly replicated) models of trade policy include the first premise but not the second. The popular models are inconsistent with the actual conduct of trade policy. We also present public-choice perspectives on strategic trade policy, the most-favored nation clause, preferential trading, duty-free zones, globalization, and direct voting on trade policy, and we review and interpret empirical evidence.
Keywords: F13; 330; political support; rent creation; budgetary revenue; trade negotiations